Manajemen Risiko Rantai Pasok Produk Halal Pada Komoditas Daging Ayam - Widyaningsih, Dwi Ayu; Nugroho, Anton Priyo (JURNAL AGROINDUSTRI HALAL, 2024)
This study aims to analyze the supply chain management of halal products in the Yogyakarta Chicken Processing Region. The type of research used is a combination model/concurrent embedded design research. The method of House of Risk as the integration of Failure Models and Effect Analysis (FMEA) method was used in this research. The results of the research showed that the percentage of risk agents was used as the main factors including the risk agent A26, (Narrow Production Space) with a percentage of 12%, A27 with a percentage of 12% (Over Stock Capacity), A20 (negligence of the officer infollowing the SOP), A31 (Product damaged in shipping), A32 (Bad delivery vehicle), A34 (Company compensation to consumers for not meeting the consumer demand). Based on the results of calculations in the House of Risk model phase 2, the ranking of preventive actions that must be carried out first includes (PA 4) conducting training for workers, (PA 3) adding refrigeration machines, (PA 1) expanding production, (PA6) leasing transportation equipment, (PA2) managing production capacity, (PA7) having a clear agreement regarding the sale and purchase agreement.